Toll-like receptor 4 plays a vital role in irritable bowel syndrome: a scoping review - Wan, Xuemeng; Wang, Liyuan; Wang, Zhiling; Wan, Chaomin (Frontiers in Immunology, 2024)
BackgroundIrritable bowel syndrome (IBS) is a common gastrointestinal disease. Recently, an increasing number of studies have shown that Toll-like receptor 4 (TLR4), widely distributed on the surface of a variety of epithelial cells (ECs) and immune sentinel cells in the gut, plays a vital role in developing IBS.ObjectivesWe sought to synthesize the existing literature on TLR4 in IBS and inform further study.MethodsWe conducted a systematic search of the PubMed, Embase (Ovid), Scopus, Web of Science, MEDLINE, and Cochrane Library databases on June 8, 2024, and screened relevant literature. Critical information was extracted, including clinical significance, relevant molecular mechanisms, and therapeutic approaches targeting TLR4 and its pathways.ResultsClinical data showed that aberrant TLR4 expression is associated with clinical manifestations such as pain and diarrhea in IBS. Aberrant expression of TLR4 is involved in pathological processes such as intestinal inflammation, barrier damage, visceral sensitization, and dysbiosis, which may be related to TLR4, NF-κB, pro-inflammatory effects, and CRF. Several studies have shown that many promising therapeutic options (i.e., acupuncture, herbs, probiotics, hormones, etc.) have been able to improve intestinal inflammation, visceral sensitization, intestinal barrier function, intestinal flora, defecation abnormalities, and depression by inhibiting TLR4 expression and related pathways.ConclusionTLR4 plays a crucial role in the development of IBS. Many promising therapeutic approaches alleviate IBS through TLR4 and its pathways. Strategies for targeting TLR4 in the future may provide new ideas for treating IBS.